Evaluation of an E. coli Cell Extract Prepared by Lysozyme‐Assisted Sonication via Gene Expression, Phage Assembly and Proteomics. (29th July 2021) - Falgenhauer, Elisabeth; von Schönberg, Sophie; Meng, Chen; Mückl, Andrea; Vogele, Kilian; Emslander, Quirin; Ludwig, Christina; Simmel, Friedrich C.
Abstract: Over the past decades, starting from crude cell extracts, a variety of successful preparation protocols and optimized reaction conditions have been established for the production of cell‐free gene expression systems. One of the crucial steps during the preparation of cell extract‐based expression systems is the cell lysis procedure itself, which largely determines the quality of the active components of the extract. Here we evaluate the utility of an E. coli cell extract, which was prepared using a combination of lysozyme incubation and a gentle sonication step. As quality measure, we demonstrate the cell‐free expression of YFP at concentrations up to 0.6 mg/mL. In addition, we produced and assembled T7 bacteriophages up to a titer of 10 8  PFU/mL. State‐of‐the‐art quantitative proteomics was used to compare the produced extracts with each other and with a commercial extract. The differences in protein composition were surprisingly small between lysozyme‐assisted sonication (LAS) extracts, but we observed an increase in the release of DNA‐binding proteins for increasing numbers of sonication cycles. Proteins taking part in carbohydrate metabolism, glycolysis, amino acid and nucleotide related pathways were found to be more abundant in the LAS extract, while proteins related to RNA modification and processing, DNA modification and replication, transcription regulation, initiation, termination and the TCA cycle were found enriched in the commercial extract. Abstract : E. coli extracts can be prepared using a simple combination of lysozyme incubation and ultrasonication. We evaluate their performance in cell‐free protein expression via the expression of reporter proteins, the assembly of bacteriophages, and using proteomics. Our results show a synergistic effect of both lysis methods.